Mining's contested future :employee and community participation in South Africa's mining charters - Du Plessis, Gideon Edward (My University, 2019)
This research report examines a multi-stakeholder attempt by the Department of Mineral Resources (DMR) to introduce a range of institutional structures to ensure meaningful participation in the transformation of the mining industry. The majority of South Africans were systematically marginalised and thus prevented from meaningful participation and ownership in the mining sector through colonial rule and the exclusionary policies of apartheid. To redress these historical inequalities, the DMR developed the Minerals and Petroleum Resources Development Act (28 of 2002) (MPRDA) and the Broad-Based Black Economic Empowerment Charter for the South African Mining and Minerals Industry ("Mining Charter") as a regulatory instrument in 2004. To increase employee participation and development of the mining community, the Act introduced compulsory future forums and social and labour plans to complement the objectives of the Mining Charter. The latter was developed with specific measurable targets in mind to effect transformation of the industry. The Department of Mineral Resources and Energy1 (DMRE) conducted a comprehensive assessment of the progress of transformation in the mining industry in 2009 and measured it against the objectives and agreed targets contained in the Mining Charter (Department of Mineral Resources, 2004). The identified shortcomings resulted in the publication of a revised charter in 2010. A further assessment, conducted in 2015, identified shortcomings in the implementation of the various elements of the revised charter. Against this backdrop, the DMR initiated a process to review the Charter with the intention to further strengthen the Mining Charter as a tool for effecting meaningful broad-based transformation of the mining and minerals industry. The initial review process, which commenced in 2016, was a failure in terms of social partner participation and subsequently, a second (and more inclusive) review process was enacted in 2018. This report investigates the process of constructing the Mining Charter (Mining Charter III, 2018) and assesses the extent to which meaningful participation (decision-making and financial terms) has been introduced in the mining sector by means of the revised Charter. At the time of the negotiations, the department was called the Department of Mineral Resources (DMR) – which was changed to the Department of Mineral Resources and Energy (DMRE) in June 2019. DMR and DMRE will be used interchangeably depending on the context. Past attempts at the institutional transfer of the German co-determination system in South Africa failed because they did not account for South Africa’s distinct industrial relations traditions and the socio-economic context. The researcher demonstrates how the clause providing for employee and community representation on company boards was removed from the final Charter and why the innovative attempt to include the “community” in charter consultations failed to gain support. On the positive side, the failed employee share ownership plans (ESOPs) will be replaced with an employee ownership and shareholding scheme provided for in the new charter, where mining employees will receive 5% carried interest shares, at no cost to the employee. This report also discusses the social partners’ responses to the abovementioned provision. Mine communities will furthermore become the beneficiaries of 5% carried interest shares or enjoy the equity equivalent thereof. Furthermore, a trust is to be established to strengthen social and labour plans with community and company representatives that will jointly identify and implement projects. This means that mining communities will receive a formal avenue to influence decision-making about development projects. Despite the attempt to increase ownership and meaningful participation through the new Charter, the challenges of transformation in the South African mining sector go well beyond traditional notions of employee participation and community development. There is also the migrant labour system, a legacy of discriminatory laws that disrupted communities and family life, but also created the dynamic of “us” and “them” between host communities and communities from labour-sending areas. The research report also focuses on the types of complexities adding to the mining industry’s contested future.
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Arts (in the field of Labour Policy and Globalisation).
Keywords: Gold mines and mining--South Africa; Mineral industries--South Africa